Hydroxyapatite as Remineralization Agent for Children's Dental Care - Meyer, Frederic; Enax, Joachim; Amaechi, Bennett Tochukwu; Limeback, Hardy; Fabritius, Helge-Otto; Ganss, Bernhard; Pawinska, Malgorzata; Paszynska, Elzbieta (Frontiers in Dental Medicine, 2022)
Children are prone to develop dental caries. This is supported by epidemiological data confirming early childhood caries (ECC) as a highly prevalent disease affecting more than every second child worldwide. ECC is known to result from an imbalance between re- and demineralization where demineralization dominates due to frequent acid production by cariogenic bacteria present in oral biofilms. The application of oral care formulations containing remineralizing agents help to prevent dental caries. As young children are sensitive and usually swallow (intended or unintended) a majority of toothpaste or other oral care products during daily dental care, all ingredients, especially the active ones, should be non-toxic. Biomimetic hydroxyapatite [HAP; Ca5(PO4)3(OH)] is known to have favorable remineralizing properties combined with an excellent biocompatibility, i.e. it is safe if accidently swallowed. Several clinical trials as well as in situ and in vitro studies have shown that HAP remineralizes enamel and dentin. Remineralization occurs due to deposition, on tooth surfaces, of HAP particles that form mineral-mineral bridges with enamel crystals, but also indirectly through calcium and phosphate ions release as well as HAP’s buffering properties in acidic environments (i.e. in plaque). HAP induces a homogenous remineralization throughout the subsurface enamel lesions. This review summarizes the current evidence showing HAP as an effective remineralizing agent in oral care products for children. Studies showing additional beneficial effects of HAP such as the reduction of biofilm formation and the relief of hypersensitivity in children with molar incisor hypomineralization (MIH) are reviewed. It can be concluded that HAP is an effective and safe remineralizing agent for child dental care.